Stroke Center Certification Is Associated With Improved Guideline Concordance. (November 2019) - Jasne, Adam S.; Sucharew, Heidi; Alwell, Kathleen; Moomaw, Charles J.; Flaherty, Matthew L.; Adeoye, Opeolu; Woo, Daniel; Mackey, Jason; Ferioli, Simona; Martini, Sharyl; de los Rios la Rosa, Felipe; Kissela, Brett M.; et al.
Measurement of quality of stroke care has become increasingly important, but data come mostly from programs in hospitals that choose to participate in certification programs, which may not be representative of the care provided in nonparticipating hospitals. The authors sought to determine differences in quality of care metric concordance for acute ischemic stroke among hospitals designated as a primary stroke center, comprehensive stroke center, and non-stroke center in a population-based epidemiologic study. Significant differences were found in both patient demographics and in concordance with guideline-based quality metrics. These differences may help inform quality improvement efforts across hospitals involved in certification as well as those that are not.